KINERJA KEUANGAN TERHADAP EFFECTIVE TAX RATE SEKTOR INFRASTRUKTUR, UTILITAS, DAN TRANSPORTASI DI INDONESIA - Gunawan, Hadi; Evi Marlina, Maria Assumpta; Ismawati, Anastasia Filiana (Accounting Study Program, Universitas Ciputra Surabaya, 2020)
This research has been conducted to analyze the effect of financialperformance on the effective tax rate. The effective tax rate is the determinantof the company’s income tax percentage payment. This research choosesinfrastructure, utility and transportation sectors companies, considering themission of the government era of Jokowi namely equitable development. Inaddition, the Business Entity Development Cooperation (KPBU) has beenconducted to accelerate the realization of this equitable development. Therole of the private sector is also used in equitable development. The writer isinterested in observing whether the taxes paid have been effective or not.The independent variables in this study are profitability, intensity fixed assets,leverage and firm size, the dependent variable of this study is the effectivetax rate. The sample of this research is companies in the infrastructure,utility and transportation sectors which are listed on the Indonesia StockExchange (IDX) with the research period 2014–2018. Data collection usespurposive sampling method. The population used in this study is 52 companies.Based on the results of observation, the sample that can be used in thisstudy is 42 companies. This study uses data analysis multiple linear regression.The results of this study indicate that profitability has a negative effect,the intensity of fixed assets a negative effect, leverage has a positiveeffect, and company size has a negative significant effect on effective taxrate.